PENINGKATAN KEAKTIFAN BELAJAR MATEMATIKA MELALUI METODE PENEMUAN TERBIMBING PADA SISWA SEMESTER IIKELAS IV SDN GULANGPONGGE 02 PATI TAHUN PELAJARAN 2014/2015 - SUNHERMI, ANNIK; Dra. Sri Gunarsi,, SH. MH (2017)
The purpose of this study is to enhance the activeness of learning mathematics students through guided discovery method.This study is divided into two cycles of the first cycle and the second cycle, each consisting of 2 meetings. Cycle I held on 26 and February 28, 2015 while the second cycle was held on 5 and March 7, 2015. The result is that after the first cycle executed an increase in the activity to 66%. Once the researchers conducted the second cycle the result of significant increased activity of which competence student count has reached 93%. With the results, researchers feel the study was sufficient to meet the target of achieving the learning activity of students that only 85%. The conclusions of this research is the use of guided discovery method can enhance the activity of learning math fourth grade SDN Gulangpongge 02 Gunungwungkal Pati second semester of the academic year 2014/2015.